Service Excellence Training: Enhancing Professionalism in the Culinary Service Industry at Omboburi Space : Pelatihan Service Excellence: Peningkatan Profesionalisme Pelayanan di Industri Kuliner pada Omboburi Space - Sofiani, Sofiani; Berutu, Feronika; Adijaja, Josephine Valerie; Maqdalena, Candy (Institut Riset dan Publikasi Indonesia, 2026)
Service quality in the culinary industry is a key factor in creating customer satisfaction and business sustainability. Omboburi Space, as a hospitality-based creative space, still faces challenges related to inconsistencies in service standards, particularly in grooming, service sequence, and complaint handling due to differences in employees’ backgrounds. This community service program aims to enhance service professionalism through service excellence training using an interactive and practical approach. The activities included needs assessment, development of hospitality-based training materials, and an online workshop conducted via Zoom with 14 participants. The training covered personal grooming, service sequence, and complaint handling. The results of the activity indicate an increase in employees' understanding and awareness of professional service standards, as reflected in the evaluation scores: Personal Grooming Understanding at 3.85, Service Sequence Execution at 3.78, Complaint Handling Ability at 4.00, and Professional Attitude Satisfaction at 3.92. This initiative demonstrates that industry-based training with a participatory approach is effective in enhancing human resource competencies in the hospitality sector and strengthening collaboration between higher education institutions and industry.